The medieval changeling : health, childcare, and the family unit - Sawyer, Rose A. (D.S. Brewer, 2023)
"The first comprehensive study of medieval changelings and associated attitudes to the health and care of children in the period.[...]This interdisciplinary study considers the idea of the changeling as a cultural construct through an examination of a broad range of medical, miracle, and imaginative texts, as well as the lives of three more conventional Saints, Stephen, Bartholomew and Lawrence, who, in their infancy, were said to have been replaced by a demonic changeling. The author highlights how people from all walks of life were invested in both creating and experiencing the images, texts and artefacts depicting these changelings, and examines societal tensions regarding infants and children: their health, their care, and their position within the familial unit."-- JSTOR.